Drug use of anti-anxiety and nutritional status college students (Research, Society and Development, 2021)
Anxiolytic drugs are drugs that act on the central nervous system producing changes in behavior, mood and cognition. The prevalence of the use of these drugs among young individuals has increased more and more and this is reflected in the university environment, where the use of these substances is widespread. The present study aimed to identify the prevalence of the use of anti-anxiety agents among college students in the city of Teresina-PI and its relation with nutritional status. This is across-sectional study with 665 college students, who filled out a questionnaire to identify the us e of anti-anxiety agents and underwent anthropometric measure men to height and weight to determine nutritional status. The associations among the different variables were made through the use of the chi-square test (p